2017
DOI: 10.1038/s41598-017-07272-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of hydroxybenzoic-based platforms as a solution to deliver dietary antioxidants to mitochondria

Abstract: Oxidative stress and mitochondrial dysfunction have been associated with metabolic and age-related diseases. Thus, the prevention of mitochondrial oxidative damage is nowadays a recognized pharmacological strategy to delay disease progression. Epidemiological studies suggested an association between the consumption of polyphenol-rich diet and the prevention of different pathologies, including diseases with a mitochondrial etiology. The development of mitochondrial-targeted antioxidants based on dietary antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 56 publications
3
51
0
Order By: Relevance
“…The reaction was followed by TLC [silica gel, ethyl acetate:methanol (9:1) and dichloromethane:methanol (9:1)]. The procedure was adapted from the literature (Brown et al, 2007 ; Teixeira et al, 2017b ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reaction was followed by TLC [silica gel, ethyl acetate:methanol (9:1) and dichloromethane:methanol (9:1)]. The procedure was adapted from the literature (Brown et al, 2007 ; Teixeira et al, 2017b ).…”
Section: Methodsmentioning
confidence: 99%
“…DPPH • radical scavenging activity was evaluated as previously described (Teixeira et al, 2017b ). The IC 50 values were determined in triplicate from the dose-response inhibition curves and are expressed as mean ± standard deviation (SD).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondria are considered the powerhouses of the cell, because they enclose important energy-producing metabolic pathways (Pereira et al, 2009;Picard et al, 2016). Besides ATP production, mitochondria display other important roles, including intracellular calcium (Ca 2þ ) regulation (Arduino et al, 2017), as well as redox and apoptotic signaling pathways (Smith et al, 2012;Teixeira et al, 2017). Decline in mitochondrial function has been associated with a wide range of human pathologies (Wallace et al, 2010), while alterations caused by drug toxicity have been extensively demonstrated (Marroquin et al, 2007;Masubuchi et al, 2006;Ong et al, 2007;Swiss and Will, 2011;Tirmenstein et al, 2002).…”
mentioning
confidence: 99%